2018
DOI: 10.1097/brs.0000000000002604
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Supine Lateral Radiographs for Assessment of Lumbar Segmental Instability in Degenerative Lumbar Spondylolisthesis

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 31 publications
0
50
2
2
Order By: Relevance
“…Incorporation of a supine lateral radiograph in place of extension radiograph can improve the understanding of segmental mobility when evaluating degenerative spondylolisthesis. [ 1 ] Landi suggested that DXR in flexion and extension performed in recumbent position (RDXR). With the patient lying along his side, it can reduces the augmented muscular tone of the paravertebral muscles in patients with low back pain or sciatic pain and might discover hypermovements hidden by antalgic contractions when investigated with DXR obtained in standing position.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of a supine lateral radiograph in place of extension radiograph can improve the understanding of segmental mobility when evaluating degenerative spondylolisthesis. [ 1 ] Landi suggested that DXR in flexion and extension performed in recumbent position (RDXR). With the patient lying along his side, it can reduces the augmented muscular tone of the paravertebral muscles in patients with low back pain or sciatic pain and might discover hypermovements hidden by antalgic contractions when investigated with DXR obtained in standing position.…”
Section: Resultsmentioning
confidence: 99%
“…B. im Sitzen mit maximal nach vorne gebeugtem Oberkörper) durchzuführen. Ein Vergleich mit der bestehenden Schnittbildgebung, die im Liegen erfolgt, ist ausreichend, sodass die Reklinationsaufnahme keinen weiteren Informationsgehalt bringt [7].…”
Section: Caveunclassified
“…Spondylolisthetic parameters: 1) slip degree (SD), measured as the slipped distance of L4 divided by the length of L5 upper endplate; 2) anterior disc height (ADH), measured as the distance from L5 anterior upper corner to L4 lower endplate; 3) posterior disc height (PDH), measured as the distance from L4 posterior lower corner to L5 upper endplate; 4) slip angle (SA), de ned as the angle between L4 lower endplate and L5 upper endplate; 5) slip angle motion (SAM), de ned as the absolute value of subtraction between slip angles in radiograph (standing) and T2-weighted MR image (supine); and 6) slip degree motion (SDM), de ned as the absolute value of subtraction between slip degrees in radiograph and T2weighted MR image. [15,16] Spino-pelvic parameters: 1) lumbar lordosis (LL), measured as the angle subtended between tangents of T12 lower endplate and S1 sacral endplate; 2) sacral slope (SS), measured as the angle subtended between tangent of S1 endplate and horizontal line; 3) pelvic tilt (PT), de ned as the angle between the vertical and a line from the center of the femoral heads to the midpoint of the sacral endplate; 4) pelvic incidence (PI), de ned as the angle subtended between a line perpendicular to the sacral plate at its midpoint and a line connecting this point to the axis of the femoral heads; 5) thoracic kyphosis (TK), de ned as the angle between the perpendicular of T5 upper endplate and the perpendicular of T12 lower endplate; and 6) sagittal vertical axis (SVA), de ned as the distance from C7 plumb line to superior corner of the sacral endplate ( Figure 2). [17,18] 1.3Quality of Life Assessment Quality of life assessment was performed based on the statistics and analysis of VAS and ODI scale.…”
Section: Patient Case Selectionmentioning
confidence: 99%